One-Pot Synthesis of 3,4-Dihydropyrimidin-2-(1H)-ones Using Nickel Chloride as a Catalyst - B. More, Uttam (Asian Journal of Chemistry, 2011)
An efficient one pot synthesis of 3,4-dihydropyrimidin-2-(1H)-ones from an aldehyde, b-ketoester and urea/thiourea, using nickel chloride pentahydrate is described. The protocol is described using three different sets of reaction conditions. The method provides much improved modification of original Biginelli reaction, in terms of high yield, short reaction time and simple workup procedure.